(untitled) (Orinoquia, 2020)
This study was aimed at determining follicular fluid (FF) protein expression and its relationship with oocyte quality. FF and oocytes were obtained by dissection and follicular aspiration of the ovaries from fifty-two commercial Zebu from a slaughterhouse. Oocyte quality was measured by cytoplasmic aspect and cumulus cells and FF protein profile by SDS-PAGE. The SAS statistical package’s PROC MEANS and analysis of variance (ANOVA) were used for descriptive analysis and the Bonferroni comparison test for assessing significant statistical differences (5% significance level); 52% of the oocytes were categorised as having I-II quality. One-dimensional SDS-PAGE analysis of FF proteins revealed 25 protein bands having 9 kDa to 240 kDa molecular weight (MW); 23 bands were expressed in <3 mm follicles, 19 bands in 3 and 6 mm follicles and 20 bands in >6 mm follicles. The 26kDa, 57kDa and 68kDa bands’ MW represented the highest FF concentration whereas only four bands (14 kDa, 34 kDa, 76 and 79 kDa MW) were found in <3mm follicles and only 2 bands (9kDa and 91 kDa MW) in >3 mm follicles. The 32 kDa band was not observed in >6mm follicles. The 26, 40, 42, 57, 68 and 240 KDa bands occurred with the greatest frequency. The protein bands which were significantly associated with oocyte quality (p<0.05) were 24, 57, 68 and 164 kDa MW for <3mm follicles, 13, 26 and 38 kDa MW bands for 3 and 6mm follicles and 26 kDa for >6mm follicles. The results indicated oocyte quality association with some protein bands.